Rocket and Groot. Tales of terror - Deibert, Amanda; Trinidad, Leo; Marvel Comics Group (New York, NY : Graphix, an imprint of Scholastic, 2024)
Determined to pull off another (not so) successful heist, Rocket and Groot find themselves trapped in the forest with a mysterious cloaked figure. The problem? They can't actually leave the woods until they tell the scariest story ever heard. Zombie aliens? Not scary enough. Bloodthirsty bugs? Nope, not good enough either. It isn't until the rest of the Guardians of the Galaxy arrive that Rocket and Groot even stand a chance!
School Library Journal, August 2024
K-3
GN350L
Keywords: Rocket Raccoon -- (Fictitious character) -- Comic books, strips, etc; Rocket Raccoon -- (Fictitious character) -- Juvenile fiction; Groot -- (Fictitious character) -- Comic books, strips, etc; Groot -- (Fictitious character) -- Juvenile fiction; Guardians of the Galaxy (Fictitious characters) -- Comic books, strips, etc; Guardians of the Galaxy (Fictitious characters) -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Fear -- Comic books, strips, etc; Fear -- Juvenile fiction; Monsters -- Comic books, strips, etc; Monsters -- Juvenile fiction; Rocket Raccoon -- (Fictitious character) -- Fiction; Groot -- (Fictitious character) -- Fiction; Guardians of the Galaxy (Fictitious characters) -- Fiction; Friendship -- Fiction; Fear -- Fiction; Monsters -- Fiction; Science fiction; Science fiction comics; Graphic novels; Comics (Graphic works)